Redes católicas y estado en la “Revolución Argentina” = Catholic and state in the networks "Argentina Revolution" - Giorgi, Guido Ignacio (Ciencias sociales y religión, 2010)
In june 1966, the civil-military-religious coup d’état known as Revolución Argentina took place, led by general Juan Carlos Onganía, who became president de facto of Argentina. In view of this new scenario, a vast group among intelectuals and experts chose to oppose the military government, while a significant number of them decided to actively support it. They were part of experiences of political and cultural activism in universities, setting up think tanks, occupying public office. In this process, the religious networks seem to be significant, especially those linked to a technocratic and “desarrollista” thinking In this article, we seek to examine the participation of catholic activists in the dictatorship known as Revolución Argentina. The trajectory of José Enrique Miguens will serve to this purpose, showing the linkages between catholic networks and the argentinean political system.